A Strategic Proposals for Developing Agile Leadership in School under Chaiyaphum Primary Educational Service Area Office 2 - Boonyota, Krittapas; Thawinkarn, Dr.Dawruwan (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2023)
This policy research is aimed (1) to create strategic proposals for developing Agile Leadership in schools and (2) to examine strategic proposals for developing Agile Leadership in school Under Chaiyaphum Primary Educational Service Area Office 2. The results showed that authentic conditions and expectation Condition of Agile Leadership Questionnaire results when considering the PNI index from descending to highest, is Stakeholder Agility, Decision-making Agility, Change Agility, Self Agility, and People Agility, respectively. And the results of creating strategic proposals for developing Agile Leadership in schools, Under Chaiyaphum Primary Educational Service Area Office 2, which consists of vision, missions, goals, objectives, strategies, and guidelines for the concept of Agile Leadership in school. Overall, there was the evaluation of Propriety at the highest level, in the Feasibility of being at the highest level, and in the Utility at the highest level.